Elevated methane levels in small intestinal bacterial overgrowth suggests delayed small bowel and colonic transit. Issue 21 (May 2018) - Suri, Jaspreet; Kataria, Rahul; Malik, Zubair; Parkman, Henry P.; Schey, Ron
Abstract : Abstract: Limited research exists regarding the relationship between small intestinal bacterial overgrowth (SIBO), small bowel transit (SBT), and colonic transit (CT). Furthermore, symptom analysis is limited between the subtypes of SIBO: hydrogen producing (H-SIBO) and methane producing (M-SIBO). The primary aims of this study are to: compare the SBT and CT in patients with a positive lactulose breath test (LBT) to those with a normal study; compare the SBT and CT among patients with H-SIBO or M-SIBO; compare the severity of symptoms in patients with a positive LBT to those with a normal study; compare the severity of symptoms among patients with H-SIBO or M-SIBO. A retrospective review was performed for 89 patients who underwent a LBT and whole gut transit scintigraphy (WGTS) between 2014 and 2016. Seventy-eight patients were included. WGTS evaluated gastric emptying, SBT (normal ≥40% radiotracer bolus accumulated at the ileocecal valve at 6 hours), and CT (normal geometric center of colonic activity = 1.6–7.0 at 24 hours, 4.0–7.0 at 48 hours, 6.2–7.0 at 72 hours; elevated geometric center indicates increased transit). We also had patients complete a pretest symptom survey to evaluate nausea, bloating, constipation, diarrhea, belching, and flatulence. A total of 78 patients (69 females, 9 males, mean age of 48 years, mean BMI of 25.9) were evaluated. Forty-seven patients had a positive LBT (H-SIBO 66%, M-SIBO 34%). Comparison of SBT among patients with a positive LBT to normal LBT revealed no significant difference (62.1% vs 58.6%, P  = .63). The mean accumulated radiotracer was higher for H-SIBO compared to M-SIBO (71.5% vs 44.1%; P  < .05). For CT, all SIBO patients had no significant difference in geometric centers of colonic activity at 24, 48, and 72 hours when compared to the normal group. When subtyping, H-SIBO had significantly higher geometric centers compared to the M-SIBO group at 24 hours (4.4 vs 3.1, P  < .001), 48 hours (5.2 vs 3.8, P  = .002), and at 72 hours (5.6 vs 4.3, P  = .006). The symptom severity scores did not differ between the positive and normal LBT groups. A higher level of nausea was present in the H-SIBO group when compared to the M-SIBO group. Overall, the presence of SIBO does not affect SBT or CT at 24, 48, and 72 hours. However, when analyzing the subtypes, M-SIBO has significantly more delayed SBT and CT when compared to H-SIBO. These results suggest the presence of delayed motility in patients with high methane levels on LBT.